The Influence of Financial Management, Social Media Use, and Product Innovation on the Performance of MSMEs in Kendaripreneur - Muhammad Fauzi; Arif Haryana; Tina Rosa (PT Bukuloka Literasi Bangsa, 2026)
ABSTRACT This study aims to analyze the influence of financial management, social media usage, and product innovation on the performance of MSMEs in Kendaripreneur. Micro businesses in Kendari face various challenges, including limited access to capital, low digital technology proficiency, and limited innovation capabilities. This study uses a quantitative method with a causal design, with the research subjects consisting of micro-business actors who are members of the Kendaripreneur community, using purposive sampling. The number of samples used in this study was 300 business actors, selected based on specific criteria to ensure the relevance of the data obtained. Data collection was conducted through questionnaires distributed to respondents, using a Likert scale to measure attitudes and perceptions of the variables under study. Data analysis was performed using descriptive analysis and Structural Equation Modeling (SEM) techniques to test hypotheses and determine the relationship between variables. The results showed that financial management had the greatest influence on MSME performance, followed by the use of social media and product innovation. Good financial management helped in making the right decisions, while social media was effective in expanding the market. Product innovation also contributed positively, although its influence was smaller. These three factors were proven to be mutually supportive in improving MSME performance after joining Kendaripreneur. Keywords: Financial Management, Social Media, Product Innovation, and Micro Business Performance